USE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN THE FIELD OF EDUCATION: CASE STUDY OF ELECTRONIC LEARNING (E-LEARNING) - Erni Ratnadewi (Celebes Education Review, 2019)
Facing the challenges of globalization in the field of education, the presence of information and communication technology has a significant influence on learning activities. The main challenge, including even the most sophisticated education system, lies in the capacity of educators to use ICT effectively in educational activities. The contribution of ICTs in building new relationships between higher education and the community, to bridge the education gap, policy makers are required to prepare strategies to produce knowledge-based skills and capacities. This type of research is qualitative. The data source consists of primary data and secondary data. Research informants are users or users of E-learning. Data collection techniques in the form of literature review of books, journals, reports on the use of information and communication technology in the education field from updated sources and observed case observations. Data analysis techniques include data reduction, data presentation and data verification. The results of the study found that the benefits of ICT for education functioned as a tool for lifelong learning; bring changes in the role of educators in teaching and the role of learners in learning; provide open access to material and interactive information through the network; eliminate time and space constraints in the learning environment; support learning and education organizations and management; and open opportunities for collaboration. Integration of ICT in e-learning into a process of internalizing values ​​in ICT learning can be transformed, so that by integrating education in e-learning as teaching material, habituation, assignment, and exemplary become integral, holistic parts, which are continually being studied, understood, practiced in everyday life. The contribution of ICT in e-learning to the success of the world of education is a strategy of implementation and professional development in the field of ICT must refer to learning and teaching activities